The Effect of Slalom Run on Increasing the Agility of Futsal Players - Wahono, Didik; Hadi, Antonius Prasetyo (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2024)
Agility is one of the main physical components in a futsal game. Slalom Run has the potential to develop the aspects necessary for improving agility. This study aims to determine the effect of Slalom Run on improving the agility of futsal players. The method used was a quasi-experiment with a one-group pretest-posttest design. The research subjects, aged 15-19 years, were chosen to represent the typical age group of futsal players. The instrument used was the zig-zag running test to measure agility levels. The results showed that Slalom Run had a significant effect on increasing agility, as evidenced by the differences in pretest and posttest results, which increased. Thus, it can be concluded that Slalom Run is efficacious in improving the agility of futsal players in this age group.